The Evaluation of User Experience UPI Digital Business Website with Usability Testing Method and System Usability Scale - Moch Gan-gan Sidiq; Rangga Gelar Guntara; Oding Herdiana (Universitas Pendidikan Indonesia (UPI), 2024)
The UPI Digital Business website, which has a domain at https://bisnisDigital.upi, is the official website of the Digital Business study program at Universitas Pendidikan Indonesia. According to the results of observing similarweb.com visitor traffic data, there are interesting findings related to the high bounce rate on the website, which is 71.35%. Likewise, from the results of informal observations of the closest website users, namely UPI Digital Business students, it was found that there were still complaints, one of which was difficulty finding some of the information needed because of the confusing navigation structure. The developer has never evaluated the experience of using the website, so it is not yet known how and how well the website can be used by current users. The research focuses on evaluating user experience in terms of ease of use by conducting usability testing and SUS tests with three aspects of ISO 9421-11 usability, namely effectivity, efficiency, and satisfaction. The result is that effectivity gets a grade “ Bad” with score of 60%, efficiency gets a score of 38%, and satisfaction gets a score of 33 out of 100.